(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2025)
Principle of Competition and its Ethical Limits.Principle of competition is a modern concept of economy and establish many rapports between all society participants. It has two sides; one god because creates premises of quality and encourages excellence production; and one harmful because invades ethical domain and determine personal rapports of people. Concept of capital and capitalism was theorised in middle of XIX Century by many socialist and liberal economists, who confront problem of limited resoursces and purpose some practical solutions of equitable distribuition of resources. They think also in direct acces of people at natural resources, reject unnecessary icreasing price of products caused by commerce. Numbers of trading increase price products and generate inflation, unloyal competition and secession between social classes and living levels. So, in Christian principle of equality of all people, of equal fundamental rights, esspecialy of those of social surviving and self determining, sustains a ethical limit of competition beacuse man is in the same time not even one material being, but one spiritual which conffer his identity.